The α‐arrestin family of ubiquitin ligase adaptors links metabolism with selective endocytosis. (1st February 2021) - Kahlhofer, Jennifer; Leon, Sebastien; Teis, David; Schmidt, Oliver
Abstract: The regulation of nutrient uptake into cells is important, as it allows to either increase biomass for cell growth or to preserve homoeostasis. A key strategy to adjust cellular nutrient uptake is the reconfiguration of the nutrient transporter repertoire at the plasma membrane by the addition of nutrient transporters through the secretory pathway and by their endocytic removal. In this review, we focus on the mechanisms that regulate selective nutrient transporter endocytosis, which is mediated by the α‐arrestin protein family. In the budding yeast Saccharomyces cerevisiae, 14 different α‐arrestins (also named arrestin‐related trafficking adaptors, ARTs) function as adaptors for the ubiquitin ligase Rsp5. They instruct Rsp5 to ubiquitinate subsets of nutrient transporters to orchestrate their endocytosis. The ART proteins are under multilevel control of the major nutrient sensing systems, including amino acid sensing by the general amino acid control and target of rapamycin pathways, and energy sensing by 5′‐adenosine‐monophosphate‐dependent kinase. The function of the six human α‐arrestins is comparably under‐characterised. Here, we summarise the current knowledge about the function, regulation and substrates of yeast ARTs and human α‐arrestins, and highlight emerging communalities and general principles. Abstract : Review : α‐Arrestins are an evolutionary conserved family of ubiquitin ligases adaptor proteins. α‐Arrestin–ubiquitin ligase complexes selectively ubiquitinate distinct plasma membrane proteins (including nutrient transporters) to initiate their endocytosis and degradation. The activity of these ubiquitin ligase adaptors is controlled by various nutrient signalling pathways. Thereby, cellular nutrient import is adjusted to the metabolic state of cells to maintain homoeostasis.